Republic of Latvia : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
This 2003 Article IV Consultation highlights that the Republic of Latvia has enjoyed continued strong economic performance since the last Article IV Consultation in January 2002. Real GDP growth was 7.9 percent in 2001 and 6.1 percent in 2002; growth has been led by investment and, more recently, consumption. Real per capita GDP now stands some 50 percent above its 1995 level. Inflation remains low and was under 1 1\2 percent in 2002. The current account deficit rose to nearly 10 percent of GDP in 2001, partly reflecting stagnant external demand and one-time factors.